Diet and the conceiving mother - Jonathan Johnson; Arsalan Aslam; M. Salman Alam; Ahmad Yaar Baig (International Journal on Women Empowerment, 2016)
There is a lack of awareness among the people of the community regarding diet during pregnancy. Diet is not only important for pregnant women but is equally important for female of pubertal age, as insufficient nutrients during this time may cause serious consequences in later life. At the community level it is important to make awareness for people about a balanced diet, it's important during reproductive age and for a pregnant woman. At the institutional level it is important to make healthcare accessible for the clients and make daily checkups possible, affordable and accessible for the pregnant women and also for the client who are in their reproductive age. In a nutshell, diet is an essential component to look after especially for women in her reproductive health and for pregnant women. Development of a proper diet plan for the mother, awareness programs on importance of diet and making healthcare accessible for the clients are some of the necessary steps needed for dealing with this problem.